2022
DOI: 10.1177/01926233221096345
|View full text |Cite
|
Sign up to set email alerts
|

The MNU Plus Testosterone Rat Model of Prostate Carcinogenesis

Abstract: Animal models of prostate cancer are essential to identify chemopreventive treatments against this major male malignancy. The N-methyl- N-nitrosourea (MNU) plus testosterone rat model of prostate carcinogenesis is a reliable animal model that recapitulates human prostate cancer in many respects and has been used extensively in chemoprevention studies with good predictive value for the results of human clinical trials. The objective of this article is to describe the induction protocol of this model, demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
1
5
1
Order By: Relevance
“…The animals of the second sacrifice were exposed to the implants for 44 weeks whereas the animals sacrificed first were only exposed for 18 weeks. This is in agreement with other studies and demonstrated that the longer the exposure to testosterone by slow-release implants, the greater the number of lesions (24,26). It is worth noting that control rats sacrificed at 61 weeks-old also developed lesions, although at a much lower frequency than those observed in treated rats.…”
Section: The Follow Up Of the Boslands' Prostate Cancer Modelsupporting
confidence: 92%
See 2 more Smart Citations
“…The animals of the second sacrifice were exposed to the implants for 44 weeks whereas the animals sacrificed first were only exposed for 18 weeks. This is in agreement with other studies and demonstrated that the longer the exposure to testosterone by slow-release implants, the greater the number of lesions (24,26). It is worth noting that control rats sacrificed at 61 weeks-old also developed lesions, although at a much lower frequency than those observed in treated rats.…”
Section: The Follow Up Of the Boslands' Prostate Cancer Modelsupporting
confidence: 92%
“…This protocol induced adenocarcinomas and atypical hyperplastic lesions in the ventral, dorsolateral, and anterior prostate. Later, Marteen C. Bosland developed a chemical carcinogen plus testosterone rat model of prostate carcinogenesis that resembles human PCa in several aspects and became the most widely used animal model (7,24). First, rats are treated daily with an antiandrogen, such as flutamide or cyproterone acetate, to inhibit prostate epithelial cell proliferation, followed by the administration of testosterone propionate to induce a synchronous cell proliferation peak.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This multistep protocol induces lesions in the dorsolateral prostate lobe of the rat, which is considered homologous to the peripheral zone of the prostate in humans, where most carcinomas develop (15). Associated with this protocol, the seminal vesicles also develop preneoplastic and neoplastic lesions, such as atypical hyperplasia and adenocarcinoma (11,12). The present article is innovative by presenting specific results of seminal vesicle lessons, correlating them with prostate lesions, and characterizing their proliferation index.…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinomas of the seminal vesicles are rare spontaneous tumors in most strains of rats and mice (9,10). However, seminal vesicle lesions, mainly adenocarcinomas, are frequently found in animal models of chemically and hormonally induced prostate cancer (PCa) (11,12). Despite this, the development of PCa lesions have rarely been correlated with seminal vesicle lesions.…”
Section: Validation Of the Rat Model Of Prostate Cancer: Correlating ...mentioning
confidence: 99%